Market-Based Monetary Policy Uncertainty. Issue 644 (3rd November 2021) - Bauer, Michael D; Lakdawala, Aeimit; Mueller, Philippe
Abstract: Uncertainty about future policy rates plays a crucial role for the transmission of monetary policy to financial markets. We demonstrate this using event studies of FOMC announcements and a new model-free uncertainty measure based on derivatives. Over the 'FOMC uncertainty cycle' announcements systematically resolve uncertainty, which then gradually ramps up again. Changes in monetary policy uncertainty around FOMC announcements—often due to forward guidance—have pronounced effects on asset prices that are distinct from the effects of conventional policy surprises. The level of uncertainty determines the magnitude of financial market reactions to surprises about the path of policy rates.